Metabolic Bone Disease due to Renal Tubular Acidosis as a Primary Manifestation in a Patient with Sjogren’s Syndrome: A Case Report - Bisht, A; Shrestha, PS; Mall, D; Wasti, K (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Renal tubular acidosis (RTA) is a group of diseases where metabolic acidosis develops due to inability of renal tubules to maintain acid base balance despite normal glomerular filtration rate. Uncorrected acidosis in RTA can cause excess osteoclastic bone resorption and result in severe metabolic bone disease like rickets, osteomalacia and pathological fracture. Sjogren’s syndrome can cause distal RTA (type 1). Here, we report a case of a 35 years old female who presented with metabolic bone disease secondary to RTA resulting from Sjogren’s syndrome.